MAJALLAH AL-AHKÂM AL-ADLIYYAH (ANALISIS HISTORIS DAN KEDUDUKANNYA DALAM SISTEM TATA HUKUM TURKI MODERN) - chamim tohari (Istinbath : Jurnal Hukum, 2017)
This research disscuss about several matters which connecting with the book of Majalla al-Ahkâm al-Adliyya as following: (1) History, system, and methods of Majalla compiling; (2) This research disscuss about several matters which connecting with the book of Majalla al-Ahkâm al-Adliyya as following: (1) History, system, and methods of Majalla compiling; (2) Critics to the Majalla book; and (3) The position of the Majalla in the law system of the modern Turkey. This research using two methods, its library research and the field research. The results of this research were: (1) The main background of the Majalla codification movement is a difficult situation to make a same desicion about the law of something by the opinion of muslim judges of the Ottoman empire. The system of the Majalla compiling consist of the technical terms in Islamic law, principles of ijtihad in Islamic law, Islamic law about muamalah (economy and transaction), and the jurisdiction law. The methods which is used in codification of Majalla is takhrij and tarjih to the most important of the Hanafi’s fiqh books. (2) Some critics made by the scholars of Islamic law to the Majalla, which is regard that the Majalla has been not achieving the standart as the sourch of privat law if it seen by the modern legislation theory. Another weakness of Majalla is it was only taken from Hanafi fiqh thought. (3) the position of Majalla book in the law system of the modern Turkey is as a spirit for implementation the newest of civil lae in Turkey, beside as the source of the informal law in the field of economy and transaction for the muslim sicuety in Turkey. Penelitian ini mengkaji beberapa hal berkaitan dengan kitab Majallah al-Ahkâm al-Adliyyah, yakni: (1) sejarah, sistem, metode penyusunan kitab majallah; (2) kritik terhadap kitab Majallah; dan (3) kedudukan kitab Majallah dalam sistem tata hukum Turki modern. Penelitian ini menggunakan dua metode, library research atau penelitian pustaka dan field research, atau penelitian lapangan. Hasil penelitian ini adalah: (1) Kodifikasi kitab Majallah al-Ahkâm al-Adliyyah oleh pemerintahan Usmaniyah di Turki. dilatarbelakangi adanya kesulitan yang dialami para hakim dalam menemukan rujukan hukum yang dapat mempersatukan pendapat mereka tentang masalah yang sama. Sistematika penyusunan kitab Majallah terdiri dari pengertian istilah-istilah dalam hukum Islam, kaidah-kaidah penetapan hukum Islam, materi hukum, serta hukum peradilan atau ushul al-hukm. Metode yang digunakan dalam penyusunan adalah metode takhrij dan tarjih terhadap kitab-kitab mu’tabarah mazhab Hanafi. (2) Beberapa kritikan muncul dari para ahli hukum Islam terhadap kitab Majallah, diantara kritikan tersebut adalah bahwa kitab Majallah tidak memenuhi standar sebagai Hukum Perdata jika dilihat berdasarkan teori perundang-undangan hukum modern. Kemelahan lainnya adalah sumber kitab Majallah yang hanya bersandar pada satu mazhab, yakni mazhab Hanafi. (3) Kedudukan kitab Majallah dalam sistem tata hukum Turki modern adalah sebagai spirit penerapan hukum perdata Turki, serta sebagai sumber hukum informal masyarakat muslim Turki dimana kitab Majallah berfungsi sebagai pedoman bermuamalah sehari-hari.